2003
DOI: 10.1038/sj.ijo.0802439
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in obese Mexican Americans treated for 1-year with orlistat and lifestyle modification

Abstract: OBJECTIVE:To evaluate the effectiveness of a culturally appropriate lifestyle intervention combined with orlistat in producing weight loss with obese Mexican-American women. SUBJECTS: Mexican-American women (N ¼ 108), aged 21-65 y, with a body mass index (BMI) Z27 kg/m 2 were randomized to 1 y of treatment with orlistat and a culturally tailored lifestyle modification intervention (OLM; n ¼ 56) or a wait-list control group (WLC; n ¼ 52). DESIGN: A randomized, controlled, open-label 12-month study. Orlistat was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The theory most frequently used to guide the interventions was the social learning theory (41.2%; Fitzgibbon, Stolley, Dyer, VanHorn, & KauferChristoffel, 2002; Poston et al, 2001; Rosal et al, 2005; Staten et al, 2004; Trevino et al, 2004; Vazquez, Millen, Bissett, Levenson, & Chipkin, 1998). Other theories or frameworks used were the social support framework (Avila & Hovell, 1994; Castro et al, 1995; Poston et al, 2001, 2003), a peer health worker model (Castro et al, 1995; Staten et al, 2004), self-change behavioral modification strategies (Avila & Hovell, 1994), a systems perspective (Castro et al, 1995), a self-determination theory and transtheoretical model (Fitzgibbon et al, 2002), a patient–provider communication model (Staten et al, 2004), a community organization framework (Thompson, Coronado, Chen, & Islas, 2006), socioecological theory (Trevino et al, 2004), social marketing and the Precede-Proceed Model (Wechsler, Basch, Zybert, & Shea, 1998), and a patient-centered counseling model (Rosal et al, 2005). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The theory most frequently used to guide the interventions was the social learning theory (41.2%; Fitzgibbon, Stolley, Dyer, VanHorn, & KauferChristoffel, 2002; Poston et al, 2001; Rosal et al, 2005; Staten et al, 2004; Trevino et al, 2004; Vazquez, Millen, Bissett, Levenson, & Chipkin, 1998). Other theories or frameworks used were the social support framework (Avila & Hovell, 1994; Castro et al, 1995; Poston et al, 2001, 2003), a peer health worker model (Castro et al, 1995; Staten et al, 2004), self-change behavioral modification strategies (Avila & Hovell, 1994), a systems perspective (Castro et al, 1995), a self-determination theory and transtheoretical model (Fitzgibbon et al, 2002), a patient–provider communication model (Staten et al, 2004), a community organization framework (Thompson, Coronado, Chen, & Islas, 2006), socioecological theory (Trevino et al, 2004), social marketing and the Precede-Proceed Model (Wechsler, Basch, Zybert, & Shea, 1998), and a patient-centered counseling model (Rosal et al, 2005). …”
Section: Resultsmentioning
confidence: 99%
“…However, authors used a varied terminology to describe the cultural qualification of the intervention: culturally appropriate (Elder et al, 2006; Poston et al, 2001, 2003; Thompson et al, 2006), culture specific (Elshaw, Young, Saunders, McGurn, & Lopez, 1994; Fitzgibbon, Stolley, Avellone, Sugerman, & Chavez, 1996; Rosal et al, 2005; Vazquez et al, 1998), or culturally focused (Castro et al, 1995). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brown, Garcia, Kouzekanani, and Hanis [61] reported a 12-month retention rate of 90% in their study involving a culturally competent lifestyle intervention targeting Mexican- Americans with type 2 diabetes. Poston et al [62] reported a 12-month retention rate of 66% in a study of 108 Mexican-American women testing a culturally tailored lifestyle modification intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, addressing lifestyle changes to prevent obesity and related diseases among ethnic minority populations remains a challenge (Corsino, et al, 2012; Faucher & Mobley, 2010; Lindberg, et al, 2012; Ockene et al, 2011; Poston et al, 2003; Rosal et al, 2011; Vincent, 2009). The Centers for Disease Control and Prevention, National Cancer Institute, and other national agencies have registries and searchable databases of evidence-based interventions (EBIs) to support their wide-spread dissemination and implementation and reach ethnic minority populations with the best approaches to addressing chronic diseases and other leading causes of mortality and morbidity (NREPP, 2015).…”
Section: Introductionmentioning
confidence: 99%